Mining of a major QTL and novel genes conferring resistance to SC3 and SC7 strains in soybean. (9th July 2021) - Chu, Jiahao; Li, Wenlong; Piao, Dongri; Kong, Youbin; Du, Hui; Lin, Feng; Li, Xihuan; Zhang, Caiying
Abstract: Soybean mosaic virus (SMV) is a serious disease in soybean production, and the cultivation of resistant variety is the irreplaceable strategy to decrease the virus damage. However, the progress of SMV molecular breeding is limited partly due to the diverse types of SMV strains, solely resistance to virus strain of variety and minor genetic effects of QTLs. In the present study, one major pleiotropic additive QTL, qSMV‐D1b, with phenotypic variation explained that 27.04%–54.23% was identified on chromosome 2, and the favourable allele was from the resistant parent "Qihuang30". Meanwhile, the allele analysis of the flanking markers showed that the favourable genotypes presented high resistance to SC3 and SC7 strains with lower disease index, while the unfavourable genotypes presented high sensitivity with higher disease index. Furthermore, six candidate genes, including four novel resistance genes, Glyma.02G121000, Glyma.02G123000, Glyma.02G123200 and Glyma.02G124700 with different expression levels between resistant and sensitive parents were discovered through transcriptome sequencing and confirmed by quantitative real‐time PCR. The resistance genes and the tightly linked molecular markers can be used for SMV breeding in soybean.